1982
DOI: 10.1111/j.1476-5381.1982.tb09309.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CARDIOVASCULAR EFFECTS OF ICI 118,587: A β1‐ADRENOCEPTOR PARTIAL AGONIST

Abstract: 1 In a preparation in which cardiovascular reflexes were prevented from occurring, ICI 118,587 (1-(p-hydroxyphenoxy)-3-p-(morpholinocarbonamido) ethylamino-2-propranol fumarate) caused dose-dependent positive chronotropic and inotropic effects upon the dog heart. 2 The increase in heart rate brought about by ICI 118,587 was about 43% of the maximum increase produced by isoprenaline.3 For a given chronotropic effect produced by either ICI 118,587 or isoprenaline, each compound produced a similar inotropic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(57 citation statements)
references
References 10 publications
5
52
0
Order By: Relevance
“…The 1-adrenoceptors on skeletal muscle are predominantly of the 032-adrenoceptor subtype (Liggett et al, 1988;Elfellah et al, 1989) and appear to be regulated during treatment with agonists or antagonists in the same way as the 1-adrenoceptors studied in lymphocytes and other tissues (Elfellah & Reid, 1987). If Xamoterol is a selective 13 1-adrenoceptor partial agonist (about 43% of the effect obtained with isoprenaline) with antagonist effects at high levels of sympathetic tone (Nuttall & Snow, 1982). It has recently been introduced for the treatment of chronic mild heart failure and muscle symptoms or CK elevation have not been features of its initial side effect profile.…”
Section: Introductionmentioning
confidence: 99%
“…The 1-adrenoceptors on skeletal muscle are predominantly of the 032-adrenoceptor subtype (Liggett et al, 1988;Elfellah et al, 1989) and appear to be regulated during treatment with agonists or antagonists in the same way as the 1-adrenoceptors studied in lymphocytes and other tissues (Elfellah & Reid, 1987). If Xamoterol is a selective 13 1-adrenoceptor partial agonist (about 43% of the effect obtained with isoprenaline) with antagonist effects at high levels of sympathetic tone (Nuttall & Snow, 1982). It has recently been introduced for the treatment of chronic mild heart failure and muscle symptoms or CK elevation have not been features of its initial side effect profile.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs the effects of ICI 118,587 on heart rate were studied during varying levels of cardiac sympathetic stimulation. At low frequencies of stimulation, ICI 118,587 increased heart rate and at high frequencies antagonism occurred with a reduction in heart rate in comparison with controls (Nuttall & Snow, 1982). An earlier study of the effects of intravenously administered ICI 118,587 on heart rate during exercise on a bicycle ergometer showed a reduction in heart rate at high workloads but the effects at rest were less clear (Harry et al, 1981) although a positive inotropic effect has been demonstrated in this situation (Marlow et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when sympathetic activity was low ICI 118,587 increased heart rate and when sympathetic tone was high, it acted as an antagonist (Nuttall & Snow, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In the elderly, diuretics may cause serious hypokalaemia and/or hyponatraemia in about 20% of patients (McLennan, 1988 (Nuttall & Snow, 1982). This provides an appropriate balance between a constant level of mild agonist activity at rest and during exercise, thereby supporting myocardial performance, and protecting the failing heart from an excessive stimulatory cardiac response, e.g.…”
Section: Introductionmentioning
confidence: 99%